Sistem Tempat Sampah Otomatis dan Notifikasi Tempat Sampah Penuh Bot Telegram - Muhammad Ayub Alghifari; Ibrahim Lammada (Peneliti.net, 2022)
Internet Of Things-Based Automatic Trash Can Bot Telegram Using the Hybrid PV Grid System is a tool that serves to make it easier for people to dispose of garbage without touching the lid of the trash can to enter trash and equipped with a notification system via the telegram bot application to notify the cleaners when the trash can is full, as well as a source of voltage the trash can is equipped with two sources of power generation using solar panels and using electricity from the State Electricity Company (PLN). This automatic trash can can be a solution to the problem of garbage dumpers who are lazy to open the lid of dirty garbage so they put garbage outside the trash can and reduce the problem of garbage accumulation because the cleaners are late to empty the trash so that the smell of garbage comes out and pollutes the surrounding air.